Kedatangan imigran-imigran China ke pantai timur Sumatera abad ke-19 : (the coming of the Chinese immigrants to East Sumatra in the 19th century) - Basarshah-II, Tuanku Luckman Sinar (Forkala-Sumut, 2010)
31 p. : il.; 21 cm